Penerapan Metode TOPSIS Pada Sistem Pendukung Keputusan Untuk Pemilihan Pegawai Teladan - Fauziyah Fauziyah; Samuel Ramos (STMIK Budi Darma, 2022)
An exemplary employee is a person who works in an office or company institution by getting a salary, but has something that can be imitated or good to emulate his actions, behavior, and so on. The problem faced in this study is in the process of selecting exemplary employees. The criteria used by the research in this study are presence, responsibility, cooperation, discipline, and initiative. In selecting exemplary employees, a Decision Support System is needed. The method used in this study is the Technicque For Order Preference By Similarity To Ideal Solution (TOPSIS) which takes into account all the criteria that support decision making to help speed up and simplify the decision-making process. The results of this study will produce a ranking order of several candidates who are appointed as exemplary employee candidates. The highest ranking exemplary employees are; Dermansyah alternate (V8), with a value of 0.6511